Regulating urban densification: what factors should be used? - Jacques Teller (Buildings & Cities, 2021)
Highlights Urban densification is increasingly accepted as a necessity and is important for no-net land take. Densification occurs in many places, especially fast-growing cities with a combination of demographic change, economic pressure and large transport infrastructure projects. The costs and benefits of density require a nuanced understanding: potential direct, indirect and cumulative effects (environmental, economic and social), both on- and off-site. The optimisation of densities implies a need to identify the conditions that can create the most value for the city, specify the places most appropriate for future inhabitants and activities, and promote spatial justice. The papers published in this special issue converge in depicting urban densification as a complex, nonlinear process, which has to be addressed at various scales. Multifactorial metrics of density are superior to aggregated ones because they offer a better understanding of the urban forms and how they are experienced by inhabitants and users. Both hard and soft densification have to be duly monitored and regulated if cities are to avoid overcrowding of places and buildings, which can be detrimental to urban resilience. The relation between urban densification and housing affordability is a critical factor that policymakers must address.